Gowa Regency BKPSDM Strategy in the Implementation of Personnel Management Information System (SIMPEG) - Fiqra Arla Muhzaib; Herlina Sakawati; Sulmiah; Anisa Fitri; Putri Dzakilla Handayani (Perkembangan Kajian Sosial, 2025)
This study aims to analyze the strategies implemented by the Gowa Regency BKPSDM in the implementation of the Personnel Management Information System (SIMPEG). The approach used is qualitative with a case study design, referring to Fred R. David's strategic management theory which includes annual goals, policies, resource allocation, and conflict management. Data was collected through interviews with key informants, direct observation, and supporting documentation. The results of the study show that the implementation of SIMPEG in Gowa Regency is effective with the achievement of annual goals through the E-Performance system. Internal policies are the guidelines for administrative control, while resource allocation is supported by competent human resources, adequate infrastructure, and a sustainable budget. Conflict management is carried out through open communication and cross-OPD coordination. However, there are still challenges to the digital literacy of senior employees and network stability. The recommendations of this research include increasing digital literacy and integrating data between agencies to strengthen the sustainability of technology-based personnel systems.